NEUROCOGNITIVE IMPAIRMENT IN HIV/AIDS: A CONCEPTUAL FRAMEWORK - Linlin Lindayani; Anastasia Anna; Nai-Ying Ko (Belitung Raya Foundation, Indonesia, 2018)
HIV-associated with neurocognitive disorder (HAND) is a major interest issues worldwide, as results from introduction of Highly Active Antiretroviral Therapy (HAART) and increasing life expectancy. However, previous studies have been limited by lack of a guiding framework. The purpose of this review was to provide a conceptual framework to guide studies of neurocognitive impairment in patients with HIV/AIDS. A literature search was conducted of articles published from 1998 through December 2015 using the PubMed, Embase, Cochrane Library and Ebscohost databases on evaluating the problem of neurocognitive impairment in HIV. This search resulted in a total of 36 articles. Evidence has indicated that there are neurobiological changes and brain abnormalities among people living with HIV/AID, which may affect cognitive functioning. Being infected by HIV and increased age are independently factors on HAND. However, there is remaining unclear the effect of HAART, is protective factors or risk factors of HAND and its consequence on quality of life among patients with HIV/AIDS. Considering the major issues in above, patient with HIV/AIDS is vulnerable population for developing HAND that might have been resulted to under report. Future studies focus on exploring HAND is necessary especially from low income countries where the accessibility to HAART are limited.